Investigating the Palaeolithic landscapes and archaeology of the Jizan and Asir regions, south-western Saudi Arabia - Inglis, Dr Robyn; Sinclair, Dr Anthony; Shuttleworth, Dr Andrew; Alsharekh, Dr Abdullah; Devès, Dr Maud; Al Ghamdi, Dr Saud; Meredith-Williams, Dr Matthew; Bailey, Prof. Geoff (Proceedings of the Seminar for Arabian Studies, 2014)
The archaeology of the Arabian Peninsula is pivotal to understanding the timing and mode of dispersals of hominin populations from Africa, with growing evidence supporting a 'Southern Route' across the Hanish Sill in the southern Red Sea. Yet despite recent key discoveries, our understanding of the hominin occupation of the Peninsula remains patchy. This situation is particularly marked in coastal south-western Saudi Arabia, a key region in dispersal debates given its proximity to the proposed Southern Route. Identification of the routes and conditions of hominin dispersals from Africa has focused on reconstructing broad-scale climatic and vegetation zones. Yet physical landscapes are also critical to palaeoenvironmental reconstruction at the local scale. They can moderate or amplify climatic influence, and modify the distribution of plant and animal resources. The DISPERSE project aims to develop systematic methods for reconstructing Palaeolithic landscapes on a variety of geographical scales, and their impact on patterns of human evolution and dispersal. This paper reports the preliminary results of archaeological and geomorphological survey carried out in February-March 2013 in the and Asir regions, south-western Saudi Arabia. Satellite imagery was used to identify areas of potential preservation and visibility of Palaeolithic sites, as well as key geomorphological features to inform landscape reconstruction. ESA, MSA, and potentially later artefacts were recorded at a number of locations and geographical settings in the region. These sites are placed within the developing model of landscape evolution, and preliminary hypotheses of hominin landscape use and technological aspects are outlined. These hypotheses will be tested through future survey seasons, ultimately allowing assessment of the factors controlling human occupation and dispersal.